2011
DOI: 10.1111/j.1758-5872.2011.00141.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of duration of untreated psychosis on the clinical course and neurocognitive features of schizophrenia

Abstract: Introduction Prolonged duration of untreated psychosis (DUP) is one of the negative factors in the course of schizophrenia. The purpose of our study was to detect the long‐term effects of DUP on the clinical and neurocognitive features of schizophrenia patients. Methods One hundred and sixty‐two schizophrenia patients were divided into two groups (short and long‐term DUP) according to the median duration (<6 months). The groups were then stratified according to duration of illness (DI) as short‐term (≤10 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The findings by Kaymak et al were in line with the current study. 26 Ran et al found an association of longer DUP with higher age, being unmarried, living alone, and having lower educational achievements ( p < .01). 8 Other studies found that untreated patients were more among 15–29 year olds (84%) than higher age groups; 27 were mostly males; 28 were artisans, followed by students and unemployed; 29 belonged to urban areas; 30 had more positive family psychiatric history (53.8%–55.1%), 29 , 30 and had an AoO of 26.0 ± 8.9 years.…”
Section: Discussionmentioning
confidence: 98%
“…The findings by Kaymak et al were in line with the current study. 26 Ran et al found an association of longer DUP with higher age, being unmarried, living alone, and having lower educational achievements ( p < .01). 8 Other studies found that untreated patients were more among 15–29 year olds (84%) than higher age groups; 27 were mostly males; 28 were artisans, followed by students and unemployed; 29 belonged to urban areas; 30 had more positive family psychiatric history (53.8%–55.1%), 29 , 30 and had an AoO of 26.0 ± 8.9 years.…”
Section: Discussionmentioning
confidence: 98%
“…Clarke et al (2006) showed that the long term consequences of a prolonged untreated psychosis include a reduced likelihood of remission and reduced functional outcome, as well as increased psychopathology. Cognitive function (Alptekin et al, 2005; Tirupati et al, 2004; Üçok et al, 2006; Vyas et al, 2007), occupational functioning (Norman et al, 2007; Penttila et al, 2011), forensic risk (Large and Nielssen, 2008), subsequent psychiatric admissions (Helgason, 1990) and even smoking habits (Kaymak et al, 2012) have all been shown to be adversely affected by a long untreated psychosis. The initiation of antipsychotic medication in the first episode of psychosis results in better outcomes (May and Tuma, 1965; May et al, 1976; May et al, 1981; Wyatt et al, 1997), and the latency of that treatment is a significant predictor of time to treatment response (Loebel et al, 1992).…”
Section: Introductionmentioning
confidence: 99%